"Off–On" fluorescent sensing of organophosphate pesticides using a carbon dot–Au(iii) complex. Issue 21 (23rd March 2018) - Wang, Miao; Li, Minmin; Lu, Jia; Fan, Bei; He, Yan; Huang, Yatao; Wang, Fengzhong
Abstract : Herein, we report novel "off–on" fluorescent sensing of organophosphate pesticides using a carbon dot (CD)–Au(iii ) complex/acetylcholinesterase (AChE) system. Abstract : Herein, we report novel "off–on" fluorescent sensing of organophosphate pesticides using a carbon dot (CD)–Au(iii ) complex/acetylcholinesterase (AChE) system. The above sensor utilizes the quenching of CD fluorescence by Au(iii ) and its subsequent recovery by thiocholine, which is generated by AChE-catalyzed hydrolysis of acetylthiocholine (ATCh) and effectively scavenges Au(iii ). In the presence of organophosphates, the catalytic activity of AChE is inhibited, allowing these species to be quantified based on the decreased recovery of CD fluorescence intensity. The developed sensor was used to analyze a real pesticide-spiked sample (4.48 μM), achieving a recovery of 99.85% and exhibiting a linear response range of 0.45–44.80 μM.